An education policy paradigm that fails upper secondary school pupils - Olofsson, Jonas [Verfasser]; Panican, Alexandru [Verfasser] (My University, 2017)
"In this article, we illustrate the creation of the education policy paradigm that constitutes the framework of vocational education and training (VET) programmes, and analyse local school representatives' perception of VET in upper secondary schools in Sweden. The education policy paradigm, established through three periods of reform during the twentieth century, undervalues VET as being less worthy than general/academic education. This paradigm generates the rhetoric used by interviewed school representatives that encourages school pupils to choose the 'right' (academic) programmes in order to foster a specific citizenship competence, even if this competence is not fully compatible with labour market demands. Young people who cannot, or will not, attain the 'right' education, and thus the advocated citizenship competence, lose out in a school system where general/academic education and higher education preparatory programmes are consistently prioritised over VET. An educational system that advocates discrimination and suspicion of VET limits career options and restricts entry into the labour market, as well as risk stigmatising pupils undertaking VET; this paradigm is neither justified nor democratic." (authors' abstract; BIBB-Doku)
Keywords: S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; Berufsbildungspolitik; Sekundarstufe II; Berufsausbildung; Image; Attraktivität; Studium; Akademisierung; Bildungschancengleichheit; Schweden